Anesthetic management of a patient with spinal muscular atrophy type II for scoliosis surgery: a case report - Zhuangyuan Chen; Xiaowei Chen; Xiyun Liang; Qiang Niu; Yauwai Chan; Xuebing Xu (BMC Anesthesiology)
Abstract Background Spinal Muscular Atrophy (SMA) is a rare autosomal recessive genetic disorder characterized by degeneration of motor neurons in the spinal cord, resulting in progressive limb muscle weakness, atrophy, and severe scoliosis. Clinically, it is divided into four types according to age at onset and severity. There are few cases reported in the literature presently, especially type II cases, and no expert consensus or guideline for the anesthetic management of spinal muscular atrophy (SMA) with scoliosis. This article discusses anesthesia management and intraoperative considerations for this patient, as well as how to help the patient reduce perioperative complications. To the best of our knowledge, this is the first case of continuous thoracolumbar dorsal ramus nerve block for pain relief after scoliosis surgery in a patient with spinal muscular atrophy type II. Case presentation We described a 17-year-old patient with spinal muscular atrophy scoliosis (SMA type II) who underwent posterior scoliosis osteotomy and orthopedic laminectomy and fusion under general anesthesia without muscle relaxants, A series of optimized anesthesia management measures were successfully implemented, aiming to reduce perioperative related complications. After the operation, continuous thoracolumbar dorsal ramus nerve block was carried out and achieved a good analgesic effect. The patient was discharged 33 days after hospitalization. It is indicated that anesthesia management for patients with SMA is a real challenge for all anesthesia providers. Conclusions For patients with SMA undergoing scoliosis surgery, total intravenous anesthesia without muscle relaxants and continuous thoracolumbar dorsal ramus nerve block after surgery have been proven to be both efficient and safe. It is also crucial to implement preoperative multidisciplinary consultation, lung-protective ventilation strategy, appropriate anesthetic drugs, reasonable blood transfusion scheme, as well as strengthened postoperative monitoring and multimodal analgesia.